2019
DOI: 10.1084/jem.20182375
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell imaging of CAR T cell activity in vivo reveals extensive functional and anatomical heterogeneity

Abstract: Cazaux et al. use intravital imaging to dissect anti-CD19 CAR T cell activity. This study uncovers both anatomical and functional diversity in the outcome of anti-CD19 CAR T cell interactions with tumor cells impacting engraftment, killing dynamics, and tumor immunoediting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 33 publications
8
120
2
Order By: Relevance
“…[24] Together, our in vitro data and the in vivo model confirm the importance of CAR T trafficking in promoting tumor-cell killing. Our results confirm that trafficking is a robust phenomenon that is independent of CAR T density.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…[24] Together, our in vitro data and the in vivo model confirm the importance of CAR T trafficking in promoting tumor-cell killing. Our results confirm that trafficking is a robust phenomenon that is independent of CAR T density.…”
Section: Discussionsupporting
confidence: 64%
“…[24] Whether the cluster formation in vivo promotes tumor-cell killing or follows the same dynamics observed in vitro remains to be investigated. We found that the size and morphology of the CAR T cell clusters are correlated with the efficiency of clearance of the tumor cells on the island.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were used on days 4-8, at which time >95% were CD8 + T cells. When indicated, T cells were retrovirally transduced to express mCherry as described 41 . Tumor-bearing mice were adoptively transferred with cultured T cells by intravenous injection of 20 × 10 6 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor-bearing mice were adoptively transferred with cultured T cells by intravenous injection of 20 × 10 6 cells. For experiments using CAR T cells, B cell lymphoma injection, conditioning and CAR T cell transfer were performed as previously described 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Extensive functional heterogeneity at the single-cell level has been observed in vivo for CAR T cell immunotherapy for B cell lymphoma in mice, with only approximately 20% of CAR T cell-B cell interactions leading to target killing 5 . The difference in killing efficiency is likely due to heterogeneity in cytotoxic potential among the CAR T cells 5 . Due to this T cell heterogeneity, T cell activation and function must be assessed at the single-cell level to fully characterize and optimize immunotherapy effects on T cells.…”
Section: Introductionmentioning
confidence: 99%